2019
DOI: 10.1371/journal.pone.0211970
|View full text |Cite
|
Sign up to set email alerts
|

Bird species detection by an observer and an autonomous sound recorder in two different environments: Forest and farmland

Abstract: Birds are commonly used as bio-indicators of the quality of environments and the changes to them. Therefore, ecologists put a lot of effort into the monitoring of their population trends. One of the methods used for bird population monitoring is autonomous sound recording. Current studies provide inconsistent results when the number of detected species by autonomous sound recorders was compared with that delivered by an observer. In our study, observers counted birds using a point-count method at 64 random poi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 58 publications
1
24
0
Order By: Relevance
“…Lastly, a caveat of this study is that we did not account for imperfect detection of species in our analyses, a factor that may depend on the habitat type in which the survey is conducted. For instance, in a recent study, Kułaga and Budka (2019) compared the number of bird species detected through human observers (in the field) and recordings by autonomous sound recorders (manually analysed by observers in the lab) within two different habitats ‐forest and farmland‐ in Poland. They reported that observers detected more species than recorders in farmland, but not in the forest (Kułaga & Budka, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, a caveat of this study is that we did not account for imperfect detection of species in our analyses, a factor that may depend on the habitat type in which the survey is conducted. For instance, in a recent study, Kułaga and Budka (2019) compared the number of bird species detected through human observers (in the field) and recordings by autonomous sound recorders (manually analysed by observers in the lab) within two different habitats ‐forest and farmland‐ in Poland. They reported that observers detected more species than recorders in farmland, but not in the forest (Kułaga & Budka, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Even non‐experts can attain high accuracy levels when using automated species classification methods (Goyette et al. ), and sound recordings are easier to process with little ornithological experience, thus increasing the number of available surveyors (Kułaga and Budka , Wheeldon et al. ).…”
Section: Practicalitymentioning
confidence: 99%
“…In more heterogeneous montane habitats, McGrann and Furnas (2016) detected only 1% of birds just visually and in forest, Darras et al 2018b detected only 4% of birds just visually. Moreover, visual detections mostly concern birds flying over the sampling point, which have large ranges and are relatively unrelated to the sampled location (Kułaga and Budka 2019). In habitats where vegetation obstructs the observers' sight, the low proportion of visual detections is primarily due to visual ranges being much shorter than acoustic ranges.…”
Section: Sampling Effectivenessmentioning
confidence: 99%
See 2 more Smart Citations